The Development of Pad-Dry-Cure Compatible Method for Preparing Electrically Conductive Copper Coated Cotton Woven Fabrics (Journal of Fiber Bioengineering and Informatics, 2013)
Electrically conductive cotton fabrics were successfully prepared by a first free radical polymerization,assisted by a conventional pad-dry-cure textile technology and subsequent electroless deposition (ELD)of copper thin layers on cotton fiber surfaces. Pad-dry-cure takes a major role in the even uptakeand penetration of the monomer [2-(methacryloyloxy)ethyl]trimethyl-ammonium chloride (METAC)solution throughout the cotton fabrics, making subsequent ELD plating of copper metal uniform. Thesurface electrical resistivity of as-prepared electro-conductive cotton fabrics varies from 10^3 to 10^{-1}Ω/sq,depending on the ELD conditions. The whole process is low cost, low chemical wastage and compatiblewith current wet processing in the textile industry, which provides a great potential in commercializationin a bulk scale.